Maria Firmina dos Reis: the risks and the boundaries of cultural markers in Úrsula - Ferreira, Isabel Cristina Rodrigues (Comunicaciones en Humanidades, 2017)
This article aims to analyze through a crossing approach to the novel Úrsula (1859) by Maria Firmina dos Reis because it wants to show how black and female characters negotiate their roles in Brazilian patriarchal and aristocratic society in the nineteenth century to explain the risks that the subdued characters and the author herself face by breaking the boundaries of gender and race imposed in this social context. These relations and representations of gender and race are constructed as cultural markers in time and space and therefore unstable and changeable. Reis questioned certain roles played by female and black characters through the intersection of social factors such as the “other”, inclusion and exclusion, i.e., the relationship of female characters (Úrsula and her mother, Luísa B.) and the three black, poor and slave characters (Túlio, Susana and Antero) with the male and white characters, respectively.